THE IMPLICATIONS OF PUBLISHER RIGHTS ON THE DIGITAL MEDIA ECOSYSTEM FROM A LEGAL PERSPECTIVE - Nugroho, Erwin Dede; Juwita, Juwita (CV. Publikasi Indonesia, 2025)
This study aims to analyze the limitations of existing copyright regulations (Laws 28/2014, 40/1999, 32/2002) that create a regulatory vacuum of publisher rights inequality and the legal implications of Presidential Regulation 32/2024 on the responsibility of digital platforms to support quality journalism. It uses a normative legal method with a legislative, conceptual, comparative (Australia-EU), and triangulation approach based on Rawls' theory, Lex Specialis (Manan), and Suzor through qualitative literature study. The results show that Presidential Regulation 32/2024 as a legitimate lex specialis operationalizes publisher rights via distribution priority (Article 5), revenue sharing of Rp105 trillion (Article 7), and the Press Council oversight committee (Articles 9-17), revolutionizing platform capitalism into collaborative co-regulation. The novelty of this research lies in the first Rawls-Lex Specialis-Suzor triangulation analyzing Presidential Regulation No. 32/2024 as Indonesia's digital constitutionalism, filling the gap in conventional copyright literature on algorithmic governance.